35. RISK FACTORS FOR PROGRESSION OF DIABETIC RETINOPATHY IN PATIENTS WITH TYPE 1 DIABETES (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluation of risk factors for progression of diabetic retinopathy (DR) in patients with insulin-dependent diabetes mellitus (type 1 diabetes).Subjects and methods: Descriptive study on 154 patients with insulin-dependent diabetes who were scheduled for eye examination from January 2023 to February 2024 at Nghe An General Friendship Hospital and Nghe An Eye Hospital.Results: There is a relationship between age of type 1 diabetes and stages of diabetic retinopathy. The younger the age of type 1 diabetes, the higher the risk of proliferative diabetic retinopathy (p9.9 (OR: 24.8; CI 3.7-215.5). There is also a threshold effect of diastolic blood pressure. That is, when diastolic blood pressure exceeds the threshold of 80 mmHg, the risk of developing proliferative diabetic retinopathy does not increase. Body mass index of patients with type 1 diabetes; Diastolic blood pressure; Duration of type 1 diabetes and fasting blood sugar levels have not shown any differences between groups of patients at different stages of diabetic retinopathy.
Keywords: Non-insulin-dependent diabetes mellitus (type 1 diabetes); diabetic retinopathy; proliferative diabetic retinopathy